Effects of Pre-Heating of Broiler Breeder's Eggs on Hatchability, Chick Quality, Overall Performance, and Welfare Traits in Broilers - Erensoy, Kadir; Sarica, Musa; Noubandiguim, Moise; Karacay, Numan (Wiley, 2024)
This study aimed to investigate the effects of varying pre-heating practices (12-h: PH12; 8-h: PH8; 4-h: PH4 and 0-h or no pre-heating: PH0) of broiler breeder's eggs prior to incubation on hatching, chick quality, overall performance, and welfare traits in broilers. A total of 960 eggs obtained from Ross 308 breeders at 45 weeks were used for pre-heating manipulations and 480 chicks for broiler experiment. Apparent fertility was higher in PH0 (94.6%) and PH4 (94.5%) treatments than in PH8 (91.6%) and PH12 (90.6%); hatchability of fertile and set eggs was higher in PH4 and PH12. PH4, PH8, and PH12 treatments significantly accelerated the average hatching time compared to PH0. General chick quality was not affected by pre-heating treatments. However, chick length was significantly lower in PH0 chicks than PH12. Pre-heating manipulations did not change the overall broiler performance. Welfare characteristics were similar among treatments, while only hock burn was better in PH8 broilers. In conclusion, pre-heating of broiler breeder eggs for 4 to 12 h improved hatching success by lowering embryonic mortality and shortened the average hatching time compared to no pre-heating, and did not cause any significant alteration in chick quality, overall performance, and welfare characteristics.
Erensoy, Kadir/0000-0002-7479-6203; Karaçay, Numan/0009-0003-9406-0361;
Keywords: Broiler Performance; Chick Quality; Hatchability; Pre-Heating; Welfare